Nutrient profile models a useful tool to facilitate healthier food choices: A comprehensive review - Santos, Mariana (2022)
Background: The term “nutrient profile” (NP) has been associated with several concepts arising from the need to regulate the choice of food products, and to allow consumers to make informed and healthier food choices. The use of NP models as a policy tool to improve public health nutrition and reduce the prevalence of non-communicable diseases, is receiving increasing attention. Scope and approach: To clarifying the importance of NP models as tools to establish public health interventions concerning consumers’ food choices, a literature review of the guiding principles to implement NP models was conducted. The covered topics include main characteristics, advantages, disadvantages, and associated gaps of the considered NP models. Key findings and conclusions: From the selected studies, a total of 85 documents were included. Nutrient profiling has a wide range of applications including front-of-pack (FoP) food labelling, regulation of food marketing to children, regulation of health and nutrition claims and school food standards. Sodium, saturated fatty acids (SFA), and total sugars were the nutrients most frequently to limit; on the contrary fibre was the most used qualifying nutrient. This review gathers, through a holistic approach, the scientific basis behind the development of the NP model, reinforcing the importance of these tools, and enabling regulators with information to establish an appropriate model.